Can men’s violence reporting behavior be improved? Evidence from a couples-based cluster randomized controlled trial in Tanzania - Halim, Nafisa; Ghanekar, Neeta; Mzilangwe, Ester Steven; Reich, Naomi; Badi, Lilian; Agarwal, Nandini; Messersmith, Lisa (Frontiers in Public Health, 2025)
PurposeIntimate partner violence (IPV) is challenging to measure due to underreporting by both men and women. The reasons why men fail to disclose their IPV perpetration in societies where such behavior is more socially accepted remain an open question. Men’s lack of awareness of how their behaviors can harm women is a contributing factor. We evaluated the impact of an intervention designed to increase men’s understanding of IPV on their ability to report it accurately, as indicated by men reporting IPV consistently with their female partners (whose reports are valid indicators of IPV).MethodsWe analyzed data from a cluster-randomized controlled trial conducted in Tanzania. A total of 450 couples from nine villages were randomly assigned to one of three arms, with each arm comprising 150 couples. In Intervention Arm 1, men participated in peer groups that explored gender relations and IPV. In Intervention Arm 2, men participated in peer groups, and communities additionally engaged in dialogues on similar topics. The Control Arm had no such activities. IPV data were collected from both partners, following ethical guidelines to ensure women’s safety. Our primary outcome includes couples reporting concordantly whether IPV occurred (couples’ concordant reporting).ResultsFrom baseline to endline, concordant reporting among couples increased for physical (31%, p = 0.002), sexual (24%, p = 0.01), and economic (22%, p = 0.05) IPV in Intervention Arm 1, accompanied by fewer men disagreeing with their female partners’ IPV reports. Similarly, in Intervention Arm 2, concordant reporting increased for physical (24%, p = 0.02) and sexual (22%, p = 0.04) IPV. There was no improvement in the concordant reporting of emotional IPV across the arms. Compared to couples in the Control Arm, those in Intervention Arm 1 had higher odds of reporting concordantly on physical (OR: 1.85, 95% CI: 0.97, 3.51, p = 0.09) and economic (OR: 1.83, 95% CI: 0.96, 3.46, p = 0.09) IPV at endline compared to baseline.ConclusionIn communities that do not link IPV to fault, men may not report IPV because they do not recognize their behaviors as abuse. Including a preamble that defines IPV in a survey questionnaire can improve men’s reporting of IPV.